Access to Justice and the Right to Democratic Participation of Victims OF Domestic Violence. From Norms to Empirics - Marotta, Julieta (The Age of Human Rights Journal, 2025)
This study employs a sociolegal approach to examine the relationship between access to justice and democratic participation by exploring both legal frameworks and the lived experiences of domestic violence victims. Analyzing international and domestic laws—including the legal empowerment approach—and conducting 54 in-depth interviews with victims, the research reveals that although progressive legal norms exist to promote participation in policy processes, these remain largely unknown and underutilized by the affected individuals. Instead, victims often engage in peer-to-peer legal empowerment, sharing rights information within their networks. The findings underscore the need for enhanced rights awareness campaigns and more accessible legal information to foster meaningful democratic engagement among vulnerable populations.